2003
DOI: 10.1016/j.str.2003.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage MS2

Abstract: Small-angle neutron scattering (SANS) has been used to extend the structural characterization of the MS2 phage by examining its physical characteristics in solution. Specifically, the contrast variation technique was employed to determine the molecular weight of the individual components of the MS2 virion (protein shell and genomic RNA) and the spatial relationship of the genomic RNA to its protein shell. A consequence of this work was to evaluate a novel particle counting instrument, the integrated virus dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(36 citation statements)
references
References 46 publications
0
34
0
1
Order By: Relevance
“…tein coats and underlying RNA core [21,[23][24][25]. Wang et al [23] have performed hydrogen-deuterium exchange measurements by incubating intact viral particles in D 2 O which clearly demonstrated that most of the polypeptide backbone of the protein coat is exchanged; an average of 67% of all peptides were found to be deuterated.…”
Section: Model Of the Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…tein coats and underlying RNA core [21,[23][24][25]. Wang et al [23] have performed hydrogen-deuterium exchange measurements by incubating intact viral particles in D 2 O which clearly demonstrated that most of the polypeptide backbone of the protein coat is exchanged; an average of 67% of all peptides were found to be deuterated.…”
Section: Model Of the Virusmentioning
confidence: 99%
“…Koning et al [24] found that the RNA formed an open network and was bound to protrusions on the inside of the MS2 capsid. Kuzmanovic et al [25] using small-angle neutron scattering of MS2 viruses found the average fraction of water in the RNA core region to be 0.81. The preponderance of experimental evidence, therefore, leads to a model of a virus which allows for the intercalation effects of water and salt.…”
Section: Model Of the Virusmentioning
confidence: 99%
“…All three types of phages have nanometer-sized structures. For example, the filamentous fd and M13 phages are nanofibers about 1 μm long and 7 nm wide (Figures 1 and 2), the icosohedral MS2 phage is a nanosphere with a diameter of about 23–27 nm,[39,43,44] and the T7 phage is made of a spherical protein coat with an inner diameter of 55 nm and a tail (19 nm in diameter and 28.5 nm long) attached to the spherical capsid. [39,40,45] The size of the phages along with the possibility to site-specifically genetically modify their surfaces by displaying a peptide or protein places the phages (Figure 1) in a unique position for templating the synthesis and assembly of nanomaterials as well as in the development of advanced nanosensors.…”
Section: Phage As a Bacteria-specific Virus And Phage Displaymentioning
confidence: 99%
“…Bei all diesen Phagen handelt es sich um nano- metergroße Strukturen. Die filamentösen fd-und M13-Phagen entsprechen beispielsweise Nanofasern von etwa 1 mm Länge und 7 nm Breite (Abbildung 1 und 2), der ikosaedrische MS2-Phage ist ein Nanokügelchen mit ungefähr 23-27 nm Durchmesser, [39,43,44] und der T7-Phage besteht aus einer kugelförmigen Proteinhülle mit 55 nm Innendurchmesser, an die ein 28.5 nm langer Schwanz mit 19 nm Durchmesser angesetzt ist. [39,40,45] Diese Größe der Phagen sowie die Fähigkeit, die chemischen Eigenschaften ihrer Oberfläche durch gentechnische Modifizierung so zu verän-dern, dass ein Peptid oder Protein an bestimmten Stellen präsentiert wird, ermöglicht es, Phagen sowohl als Template für die Synthese und den Aufbau von Nanomaterialien als auch für die Entwicklung fortschrittlicher Nanosensoren zu nutzen.…”
Section: Phagenunclassified